Role of HIV Infection Duration and CD4 Cell Level at Initiation of Combination Anti-Retroviral Therapy on Risk of Failure - Lodi,S; Phillips,A; Fidler,S; Hawkins,D; Gilson,R; McLean,K; Fisher,M; Post,F; Johnson,AM; Walker-Nthenda,L; Dunn,D; Porter,K (PLoS ONE, 2013)
Background: The development of HIV drug resistance and subsequent virological failure are often cited as potentialdisadvantages of early cART initiation. However, their long-term probability is not known, and neither is the role ofduration of infection at the time of initiation.Methods: Patients enrolled in the UK Register of HIV seroconverters were followed-up from cART initiation to lastHIV-RNA measurement. Through survival analysis we examined predictors of virologic failure (2HIV-RNA ≥400 c/lwhile on cART) including CD4 count and HIV duration at initiation. We also estimated the cumulative probabilities offailure and drug resistance (from the available HIV nucleotide sequences) for early initiators (cART within 12 monthsof seroconversion).Results: Of 1075 starting cART at a median (IQR) CD4 count 272 (190,370) cells/mm3 and HIV duration 3 (1,6)years, virological failure occurred in 163 (15%). Higher CD4 count at initiation, but not HIV infection duration at cARTinitiation, was independently associated with lower risk of failure (p=0.033 and 0.592 respectively). Among 230patients initiating cART early, 97 (42%) discontinued it after a median of 7 months; cumulative probabilities ofresistance and failure by 8 years were 7% (95% CI 4,11) and 19% (13,25), respectively.Conclusion: Although the rate of discontinuation of early cART in our cohort was high, the long-term rate ofvirological failure was low. Our data do not support early cART initiation being associated with increased risk offailure and drug resistance.